2000
DOI: 10.1149/1.1393341
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of TiN Microcoils and Microtubes by Titanizing/Nitriding of Carbon and TiC Microcoils

Abstract: Materials with a three-dimensional (3D) microcoiled structure or with a microtube morphology are not industrially available. However, we could expect novel properties from the microcoiled materials which have morphologies similar to DNA or from a microtube morphology. The growth of microcoiled carbon fibers from the vapor phase has been reported by many researchers. [1][2][3][4][5][6][7][8][9] The vapor growth of the microcoils of SiC, [10][11][12] Si 3 N 4 , [13][14][15][16] etc. have also been reported. Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
(15 reference statements)
0
2
0
Order By: Relevance
“…A schematic of the reaction tube is shown in the literature [12]. The reaction was carried out with, or without, applying a magnetic field in the reaction zone.…”
Section: Methodsmentioning
confidence: 99%
“…A schematic of the reaction tube is shown in the literature [12]. The reaction was carried out with, or without, applying a magnetic field in the reaction zone.…”
Section: Methodsmentioning
confidence: 99%
“…We have found that the carbon coils could be vapor phase titanized and nitrided at the same times to form TiN micro-coils/micro-tubes [11].…”
Section: Introductionmentioning
confidence: 94%